Sytuacja gospodarcza wsi w powiecie tarnowskim w II Rzeczypospolitej - Mierzwa, Paweł (Zeszyty Wiejskie, 2019)
The reborn Poland was a country with a definite dominance of the agricultural sector over other sectors of the national economy. The financial situation of the village had a huge impact on the development of the country’s economy. With a good situation in the agricultural sector, other areas of the economy could develop quickly. With the financial crisis in the 1930s – which the Polish village found itself in – other branches of the economy were also in a weak condition.